Mapping of Land Suitability for Rambutan (Nephelium lappaceum) in Community Agroforestry Land at Gunung Ambat Village and Simpang Kuta Buluh Village - Rahmawaty, Rahmawaty; Batubara, Ridwanti; Rauf, Abdul; Frastika, Sintike (UNIVERSITY OF LAMPUNG, 2020)
Rambutan (Nephelium lappaceum) is Sapindaceae family, commonly found in agroforestry land, owned by the community in Langkat District, North Sumatra Province as One of Multy Purpose Tree Species. This study aimed to asses and map the distribution land suitability for N. lappaceum. This research was conducted in Gunung Ambat Village and Simpang Kuta Buluh Village, Sei Bingai Sub District, Langkat Regency using survey method. The soil samples data was collected in the field based on the land unit. Land suitability assessment was evaluated using matching method. To map the distribution of land suitability, the Geographic Information System (GIS) was used. Global Positioning System (GPS) also was used in this study to record the coordinate points of each soil sample from the field. The results indicate that the actual land suitability classes for N. lappaceum were dominated by moderately suitable (S2) (97.56%) in Gunung Ambat Village and moderately suitable (S2) (52.92%) in Simpang Kuta Buluh Village. The water availability (wa) and root zone medium (rc) were the dominant limiting factor in this area.